1998
DOI: 10.1007/s002380050130
|View full text |Cite
|
Sign up to set email alerts
|

Temporalis fascialis sling - a surgical techique for the treatment of recurrent dislocation of the temporomandibular joint

Abstract: Recurrent dislocation of the temporomandibular joint is a relatively common problem for which many treatment alternatives have been described. When recurrent dislocation fails to respond to conservative treatment or pain becomes a major problem, surgical intervention is warranted. Unfortunately, current treatments are unpredictable and are associated with problems such as foreign body reactions, degeneration, and recurrent pain. We describe a new procedure, using a temporalis sling for the treatment of recurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In such a situation, conservative treatment is not successful. For the treatment of recurrent TMJ dislocation, many methods are attempted for the articular eminence, condyle or soft tissue [3][4][5][6][7][8][9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In such a situation, conservative treatment is not successful. For the treatment of recurrent TMJ dislocation, many methods are attempted for the articular eminence, condyle or soft tissue [3][4][5][6][7][8][9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…1). If this dislocation occurs as a chronic or recurrent condition, conservative treatment is not successful in a majority of patients, and surgical treatment remains the only option [1][2][3][4]. The treatment of recurrent TMJ dislocation has been varied and is aimed at repositioning the condyle and preventing further recurrences.…”
Section: Introductionmentioning
confidence: 99%
“…Other aetiological factors associated with TMJ dislocation are trauma, the use of anti-emetics and phenothiazine, which produce extra-pyramidal effects, systemic diseases such as rheumatoid arthritis, and psychogenic and neurological disorders. (6,7) . It was found that dislocation occurs more frequently in patients with TMJ internal derangement, occlusal disturbances (loss of vertical height), joint laxity and neurological disorders (8,9) .…”
Section: Introductionmentioning
confidence: 99%